2022
DOI: 10.1002/pmic.202100168
|View full text |Cite
|
Sign up to set email alerts
|

Serum starvation induces sexual dimorphisms in secreted proteins of human umbilical vein endothelial cells (HUVECs) from twin pairs

Abstract: There is growing evidence for sex and gender differences in the clinical manifestation and outcomes of human diseases. Human primary endothelial cells represent a useful cardiovascular model to study sexual dimorphisms at the cellular level. Here, we analyzed sexual dimorphisms of the secretome after serum starvation using human umbilical vein endothelial cells (HUVECs) from twin pairs of the opposite sex to minimize the impact of varying genetic background. HUVECs were starved for 5 and 16 h, respectively, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Our data are further supported by a comparative analysis of gene expression data from endothelial cells of twin pairs at birth and adult non-twins, which has shown that sex differences exist at all stages of life and that 14-25% of the overall endothelial cell transcriptome is sex-specific (Hartman et al, 2020). Beyond gene dosages, sex differences were likewise identified in secreted proteins of cell culture supernatants as well as in various cellular functions such as proliferation, angiogenesis and migration (Addis et al, 2014;Cattaneo et al, 2017Cattaneo et al, , 2021Lorenz et al, 2019Lorenz et al, , 2022. For example, we and others have found that female HUVECs have better stress tolerance and higher migratory capacity than male cells (Addis et al, 2014;Cattaneo et al, 2021;Lorenz et al, 2015Lorenz et al, , 2019.…”
Section: … and So Do Female And Male Cellssupporting
confidence: 75%
See 2 more Smart Citations
“…Our data are further supported by a comparative analysis of gene expression data from endothelial cells of twin pairs at birth and adult non-twins, which has shown that sex differences exist at all stages of life and that 14-25% of the overall endothelial cell transcriptome is sex-specific (Hartman et al, 2020). Beyond gene dosages, sex differences were likewise identified in secreted proteins of cell culture supernatants as well as in various cellular functions such as proliferation, angiogenesis and migration (Addis et al, 2014;Cattaneo et al, 2017Cattaneo et al, , 2021Lorenz et al, 2019Lorenz et al, , 2022. For example, we and others have found that female HUVECs have better stress tolerance and higher migratory capacity than male cells (Addis et al, 2014;Cattaneo et al, 2021;Lorenz et al, 2015Lorenz et al, , 2019.…”
Section: … and So Do Female And Male Cellssupporting
confidence: 75%
“…Interestingly, we found in a transcriptional study that many genes linked to the stress and immune response showed a higher expression in female cells, a result consistent with clinical findings demonstrating a stronger immune response in women (Klein & Flanagan, 2016; Lorenz et al., 2015). To reduce biological variability, we then used cells derived from cords of dizygotic twin pairs (Lorenz et al., 2019, 2022; Witt et al., 2019). These cells have the unique advantage of a similar intrauterine environment due to identical maternal conditions, and they also share some genetic background.…”
Section: Women and Men Differ…mentioning
confidence: 99%
See 1 more Smart Citation
“…This study noted that male HUVECs expressed more VEGF receptor 2 mRNA than females under standard culture conditions; however, this difference was not observed at the protein level. Other work involving long-term serum starvation suggests greater adaptation potential of female cells than male cells, owing to their sex-specific secretome (102). Given the criticality of nutrient supply for most tissue engineering applications, these data support considering the role of biological sex in vascularization.…”
Section: Signalsmentioning
confidence: 74%
“…Except for collagen, we could not find evidence for localization on the apical endothelial surface for any of these proteins in the literature. COLI 28,29 and COLV 29 were detected in the secretome of HUVECs, and the expression of COLV was shown to be regulated by shear stress in human fibrosa aortic valve ECs. 30 Early reports have also shown the presence of COLV on the apical surface of ECs.…”
Section: Discussionmentioning
confidence: 98%